THE IMPACT OF ARTIFICIAL INTELLIGENCE ON NEUROLOGICAL DIAGNOSTICS AND TREATMENT - Anvarova Sevara Mirzoxid qizi; Ismanova Arofatxon Abduldulhamidovna (TADQIQOTLAR, 2025)
Abstract. Information technologies (IT) have transformed various aspects of healthcare, particularly in the field of neurology. The use of IT enhances diagnostic precision, facilitates remote consultations, and optimizes the management of neurological diseases. This article explores the revolutionary role that AI plays in neurological diagnostics and treatment. We will examine how AI is being used to enhance diagnostic accuracy, the potential benefits it offers in personalized treatments, and the future directions of AI technologies in neurology. Through the exploration of case studies and the latest research, we will gain insight into how AI is shaping the future of neurological healthcare.